Motor imagery enhances core training effects on lumbar proprioception in elite swimmers: a randomized controlled trial - Solana-Tramunt, Mónica; Bofill-Ródenas, Ana (Frontiers in Physiology, 2025)
Lumbar proprioception is essential for executing effective movements during the undulatory underwater swimming (UUS) technique. Core exercises are commonly used to strengthen the musculature involved in UUS, and variations in sensory input and attentional focus may modulate neuromuscular responses, influencing training outcomes. This study investigated the impact of repeated maximal lumbar movements performed with closed eyes and motor imagery on lumbar proprioception in elite swimmers, compared to performing the same exercises with proper technique and controlled breathing alone. Methods: A total of 57 elite swimmers (34 males, 20.2 ± 4.2 years; 23 females, 20.7 ± 3.3 years) volunteered and completed the study. Participants were randomly assigned to two experimental groups (EG1 and EG2) and one control group (CG). All groups followed the same swimming and physical training program, with EG1 and EG2 completing additional lumbar flexion-extension exercises. Both EG1 and EG2 performed three sets of 10 repetitions at a controlled breathing pace, 6 days per week for 11 weeks. EG1 completed the exercises with eyes closed and motor imagery; EG2 performed the same exercises focusing only on technique. Lumbar joint position sense in the sagittal plane was assessed using an electrogoniometer while seated on a Swiss ball. Results: Significant group differences were found for relative repositioning error (REr) (F = 6.75, p = 0.012) and absolute error (ABSEr) (F = 7.34, p = 0.009). EG1 showed large positive effect sizes (REr d = 0.91; ABSEr d = 1.24), EG2 showed negative effects (REr d = −0.56; ABSEr d = −1.17), and CG had no meaningful changes. Conclusion: Motor imagery enhances proprioceptive accuracy beyond physical training alone. Trial Registration: NCT06747702.